Mental Health Socialization and Education to Improve Student Literacy in Vocational Colleges: A Study at Politeknik Negeri Madiun - Lala Hucadinota Ainul Amri; Dyah Ayu Kunthi Puspitasari; Whan Augustin Ainul Amri; Yogi Akbar Sunardiansyah (Universitas AMIKOM Yogyakarta, 2025)
Student mental health is a critical issue in higher education, particularly at vocational colleges, which simultaneously require academic preparedness and practical skills. This community service activity aims to improve students' mental health literacy through outreach and education integrated into the learning process at the Madiun State Polytechnic. The implementation method uses a participatory approach by integrating mental health materials into learning activities, including the delivery of basic mental health concepts, an introduction to academic stress, and adaptive coping strategies. The activities were conducted through interactive lectures, discussions, case studies, and learning reflections. The results of the activity indicate an increase in students' understanding and awareness of the importance of mental health, as well as their ability to recognize and manage academic stress more adaptively. The integration of materials into learning has proven effective because it provides a contextual and sustainable learning experience. Therefore, this activity contributes to the development of a learning-based mental health education model at vocational colleges.